2007
DOI: 10.1088/0957-4484/18/26/265402
|View full text |Cite
|
Sign up to set email alerts
|

Formation of various metal nanostructures with thermal annealing to control the effective coupling energy between a surface plasmon and an InGaN/GaN quantum well

Abstract: We demonstrate the variations of the photoluminescence (PL) spectral peak position and intensity through the surface plasmon (SP) coupling with an InGaN/GaN quantum well (QW) by forming Ag nanostructures of different scale sizes on the QW structure with thermal annealing. By transferring an Ag thin film into a nanoisland structure, we can not only enhance the PL intensity, but also adjust the SP dispersion relation and hence red-shift the effective QW emission wavelength. Such an emission spectrum control can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 11 publications
1
32
0
Order By: Relevance
“…However, it has been confirmed through IQE, time-resolved PL, and electroluminescence (EL) measurements, that an enhancement due to metal NPs based on this excitation and detection scheme can indeed be attributed to LSP-QW coupling131415161718192223. Nonetheless it is still required to exclude the contribution from the enhanced reflection of the excitation source due to Ag NPs as done in Ref.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, it has been confirmed through IQE, time-resolved PL, and electroluminescence (EL) measurements, that an enhancement due to metal NPs based on this excitation and detection scheme can indeed be attributed to LSP-QW coupling131415161718192223. Nonetheless it is still required to exclude the contribution from the enhanced reflection of the excitation source due to Ag NPs as done in Ref.…”
Section: Resultsmentioning
confidence: 96%
“…The energy out-coupling of these SPP modes into photons was later demonstrated through photoluminescence (PL) enhancement1314. Randomly distributed metal nanoparticles (NPs) have also been investigated as a way to improve the recombination rate through exciton coupling with localized surface plasmon (LSP) modes151617181920. The advantage of LSP modes comes from fact that they do not require a phase-matching condition in order to radiate the stored energy21.…”
mentioning
confidence: 99%
“…The metal NPs can be fabricated through the thermal annealing of a thin metal film. 20,21) In this situation, the size and position of metal NP are randomly distributed. Regularly arranged metal NPs of uniform size can be fabricated through nanoimprint lithography, dry etching, and liftoff process.…”
Section: Experimental Implementationsmentioning
confidence: 99%
“…NPs with the required sizes and heights can be produced by annealing at different temperatures and for different times on metal fi lms with different thicknesses, to achieve the best coupling effect with the light emitters. Yeh et al (2007) annealed three samples with initial fi lm thicknesses of 5 nm, 10 nm and 15 nm at 200 °C for 30 min and they observed that the size and heights of silver NPs were signifi cantly increased. Annealing enhances the photoluminescence intensity of the SP light emitters due to enhanced SP/QW coupling.…”
Section: Vacuum Depositionmentioning
confidence: 99%